Functions of liver natural killer cells are dependent on the severity of liver inflammation and fibrosis in chronic hepatitis C. - Emilie Fugier; Hélène Marche; Marie-Ange Thélu; Zuzana Macek Jílková; Nicolas Van Campenhout; Tania Dufeu-Duchesne; Vincent Leroy; Jean-Pierre Zarski; Nathalie Sturm; Patrice N Marche; Evelyne Jouvin-Marche (PLoS ONE)
During chronic hepatitis C virus (HCV) infection, the role of intra-hepatic (IH) natural killer (NK) cells is still controversial. To clarify their functions, we investigated anti-viral and cytotoxic activity of NK cells in human fresh liver biopsies. We compared the functions of IH-NK cells in HCV-infected and NASH patients in physiological conditions as well as after stimulation using flow cytometric and immunohistochemical analyses. Interestingly, few IH-NK cells produced anti-viral cytokine IFN-γ in HCV-infected patients similarly as in non-infected individuals. Spontaneous degranulation activity was extremely low in peripheral NK cells compared to IH-NK cells, and was significantly higher in IH-NK cells from HCV-infected patients compared to non-infected individuals. Immunohistochemical analysis revealed that perforin granules were polarized at the apical pole of IH-NK cells. The presence of CD107a and perforin in IH-NK cells demonstrated that NK cells exerted a cytolytic activity at the site of infection. Importantly, IH-NK cell functions from HCV-infected patients were inducible by specific exogenous stimulations. Upon ex vivo K562 target cell stimulations, the number of degranulating NK cells was significantly increased in the pool of IH-NK cells compared to circulating NK cells. Interestingly, after stimulation, the frequency of IFN-γ-producing IH-NK cells in HCV-infected patients was significantly higher at early stage of inflammation whereas the spontaneous IH-NK cell degranulation activity was significantly impaired in patients with highest inflammation and fibrosis Metavir scores. Our study highlights that some IH-NK cells in HCV-infected patients are able to produce INF-γ and degranulate and that those two activities depend on liver environment including the severity of liver injury. Thus, we conclude that critical roles of IH-NK cells have to be taken into account in the course of the liver pathogenesis associated to chronic HCV infection.